2015
DOI: 10.1371/journal.pone.0119211
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Major Light-Harvesting Complexes (LHCBM) of the Green Alga Chlamydomonas reinhardtii

Abstract: Nine genes (LHCBM1-9) encode the major light-harvesting system of Chlamydomonas reinhardtii. Transcriptomic and proteomic analyses have shown that those genes are all expressed albeit in different amounts and some of them only in certain conditions. However, little is known about the properties and specific functions of the individual gene products because they have never been isolated. Here we have purified several complexes from native membranes and/or we have reconstituted them in vitro with pigments extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 52 publications
9
72
0
Order By: Relevance
“…We have recently shown that this is not the case for isolated LHCII in the absence of aggregation from both plants and C. reinhardtii (18,26). Our results here show that LHCII in the membrane is not quenched in response to pH changes, and that the quenching can also not be induced by the interaction of zeaxanthin with LHCBM1.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…We have recently shown that this is not the case for isolated LHCII in the absence of aggregation from both plants and C. reinhardtii (18,26). Our results here show that LHCII in the membrane is not quenched in response to pH changes, and that the quenching can also not be induced by the interaction of zeaxanthin with LHCBM1.…”
Section: Discussionmentioning
confidence: 40%
“…The PCR product and expression vector petMHis were digested with BamHI and XhoI, ligated, and transformed into BL21 Escherichia coli for expression (42). LhcbM1 was cloned and expressed as described (26). The apoproteins were quantified using a bicinchoninic acid assay (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Ϫ1 as found for isolated LHCII trimers of C. reinhardtii (41). The complete kinetic scheme (Scheme SI2-1) also contains precursors populating the other compartments on the ps time scale, with relative amounts varying depending on excitation wavelength (Table SI1-2), and a disconnected compartment corresponding to species with ns lifetimes.…”
Section: Methodsmentioning
confidence: 95%
“…At the same time, the fluorescence lifetime decreased down to a minimum of 0.97 ns (Table 1). On the other hand, the lifetime of the sample in liposomes with a high lipid/protein molar ratio of ϳ7000:1 (0.1 g of Chl a) had a similar value compared with isolated monomeric LHCII in detergent (Table 1) (30,31). A further decrease in the amount of protein per liposome (0.05 g of Chl a equal to a lipid/protein molar ratio of ϳ14,000:1) induced the appearance of free Chls in the sample.…”
Section: Incorporation Of Chlamydomonas Reinhardtii Lhcii Intomentioning
confidence: 92%